Application of an amphoteric polymer for leather pickling to obtain a less total dissolved solids residual process. (15th December 2016) - Jia, Lu; Ma, Jianzhong; Gao, Dangge; Lyu, Bin; Zhang, Jing
Abstract: A clean approach of less total dissolved solids residual process based on an amphoteric polymer has been attempted. Amphoteric polymer was added in the pickling as experimental process. The amount of common salt reduced from 8% to 2% and the amount of basic chrome sulfate was 4%. 8% common salt was added in pickling and 4% basic chrome sulfate was added in tanning as control. The tanning waste water, wet blue and crust leathers were analysed. The results showed that the amphoteric polymer resulted in increment of Cr2 O3 content in leather by 10.8%, and the amphoteric polymer offered leather showed better chromium distribution and collagen fibers distribution properties than conventional leather. The mechanical properties, colour value and shrinkage temperature of the leather treated with amphoteric polymer were close to those of the conventional leather. What's more, the Cr2 O3 content of experimental tanning waste reduced by 53.5%, and the reduction in Cl − content is 78.3%, and the total dissolved solids in the experimental waste reduced to 178.11 g/L. From the results obtained, it is suggested that without affecting the quality of the finished leather, the amphoteric polymer offered process could reduce the pollution of tanning waste, and promote the development of cleaner production. Graphical abstract: Highlights: A clean approach to less total dissolved solids residual process based on an amphoteric polymer has been attempted. Amphoteric polymer pickling and tanning process achieved better environmental benefits than conventional process. The amphoteric polymer tanned leather showed better quality, and this technology was possible to realize industrial production.